Alemtuzumab (Campath-1H) in therapy of CLL - Rai, Kanti (Henry Stewart Talks, 2007)
Development of Campath-1H, Burroughs-Wellcome Era (BW), Millenium (LeukosSite)-Ilex Era (MI), Differences between BW era and MI era, The two main trials in the BW era: study 005 in European countries and study 009 in the USA, Responses to these trials, Complications of these trials: opportunistic infection, MI era results from 1998 and study 211 (which incorporated prophylaxis against opportunistic infections), Efficacy of Campath-1H, Examination of bone marrow biopsy specimens, Survival times, Infectious complications after first-line therapy with Campath-1H, CMV guidelines, CALGB trial
Archived at 2016/06/22